Toward Hospital Implementation of Advance Care Planning: Should Hospital Professionals Be Involved?. (February 2018) - Vanderhaeghen, Birgit; Bossuyt, Inge; Opdebeeck, Sybille; Menten, Johan; Rober, Peter
In Belgium, Advance Care Planning (ACP) is not well implemented in hospital practice. One of the premises for successful implementation is involving the adopters in the implementation process. In hospital, important adopters of ACP are physicians, nurses, social workers, and psychologists. First, this study wants to understand what the characteristics are of ACP in hospital, according to professionals. Second, this study aims to give an insight in the experienced value of ACP. Third, the experienced barriers to have ACP conversations are explored. Twenty-four interviews were taken and analyzed with Content Analysis based on Grounded Theory. Three independent external auditors surveilled the analysis. ACP in hospital exists by the grace of the initiative of the actors involved in the case. Professionals perceive fields of tension between one another; barriers to ACP communication. ACP is mainly considered valuable because it is a process that creates time for exploration and reflection.